The Sustainability of Semarang Kauman Village (When Conservation Meets Development) - Margareta Maria Sudarwani (Local Wisdom : Jurnal Ilmiah Kajian Kearifan Lokal, 2024)
Semarang has developed as a large coastal city with an important port due to its strategic and unique position. This strategic and unique position is shown by the hills at the top of the city such as Gajah Mungkur, Candi, Mrican, Mugas, Mount Sawo, Simongan and others as well as lowlands at the bottom of the city. One of the important historical ethnic villages to be appointed is Kampung Kauman, Semarang, which has a distinctive history related to the existence of the Great Mosque of Semarang. is an ancient village inhabited by local residents which began to be awakened during the reign of Ki Ageng Padang Aran. The Great Mosque of Semarang, although it is quite an old mosque, is the first mosque in the city of Semarang which was founded by Ki Ageng Padang Aran. The Great Mosque of Semarang is located in the old Semarang square complex which has the same pattern as Javanese city squares in general. There are many opinions regarding the term "kauman". There is an opinion that "kauman" comes from the word: nggone wong qoum (place of the clans), pakauman (place of residence of the clans), sing aman (safe group/people) or there is also the opinion of qo'um muddin (Islamic religious leader). Based on the opinions described above, "kauman" contains the meaning of the residence of the scholars. This study aims to examine the sustainability of residential spaces in Kauman village, both physical and non-physical characteristics and aims to optimize the potential of existing villages for urban development planning. This research uses a descriptive method based on empirical facts. The results of the Kauman Village Residential Spatial Sustainability Research are then used as needed, including development strategies and future city government decisions.